PEMBERDAYAAN PEREMPUAN DALAM PERTANIAN URBAN MELALUI AKUAPONIK DAN DIGITALISASI PEMASARAN DI KOTA PADANG - Awalina, Rahmi; Masnarivan, Yeffi; Syukri, Daimon (Jurnal Hilirisasi IPTEKS, 2025)
Women play a strategic role in the agricultural sector, particularly in supporting food security and household economies. However, limited access to agricultural technologies and low levels of digital literacy remain significant barriers to the capacity development of Women Farmer Groups (KWT). This community engagement programme aimed to empower the Jirak Serumpun Women Farmer Group in Mata Air Sub-district through the integration of aquaponic systems and digital marketing. The activities were conducted from July to September 2024 in Mata Air, South Padang District, Padang City, West Sumatra, involving 20 group members. The programme consisted of technical training in aquaponics cultivation, digital marketing workshops using social media platforms, and basic bookkeeping training using Microsoft Excel. The outcomes revealed that 85% of participants were able to independently assemble and manage aquaponic systems; a dedicated social media account was successfully activated for promotional purposes; and the group began implementing digital financial records. Moreover, the adoption of aquaponics led to a 35% increase in vegetable production and a 22% rise in average income within three months after training. This initiative not only enhanced production capacity and marketing efficiency but also reinforced women's economic autonomy at the community level. The empowerment model, based on appropriate technology and digital marketing, proved effective as a sustainable agricultural development strategy that is responsive to women's roles.